Platelet-Lymphocyte Ratio (PLR) as an Early Predictor of Severity in Acute Biliary Pancreatitis - Tahir, Muhammad Nafe Bin; Roshnik Ayub; Awaba, Hanya; Abbasi, Shehzad Ahmed; Shah, Muhammad Yousaf; Muhammad Ans (Pakistan Armed Forces Medical Journal, 2024)
Objective: To establish diagnostic precision regarding platelet-lymphocyte ratio for prophesying the severity of acute biliary pancreatitis in the early diagnostic phase, taking the Computed Tomography Severity Index as the gold standard. Study Design: Cross-sectional validation study. Place and Duration of Study: Pakistan Air Force Hospital Mushaf Base, Sargodha Pakistan, Jan to Dec 2023. Methodology: Two hundred and twenty-five (n=225) patients diagnosed with acute biliary pancreatitis lying within an age bracket of 18-70 years (male and female) were inculcated. Patients having chronic diseases such as chronic pancreatitis, diabetes mellitus, cardiovascular diseases, end-stage renal and hepatic diseases, and other causes, e.g., Trauma, Endoscopic Retrograde Cholangiopancreatography, (iatrogenic), hypertriglyceridemia, and alcohol, were excluded. All patients were treated for acute pancreatitis. Seventy-two hours after admission, all patients underwent a Computed Tomography scan for Computed Tomography Severity Index. Results: Platelet-lymphocyte ratio supported the diagnosis of severe acute pancreatitis in 99(44.0%) patients. Computed Tomography Severity Index findings confirmed severe acute pancreatitis in 93(41.33%) cases. In patients having platelet-lymphocyte ratio positive, 83 were TP, and 16 were FP. In 126 platelet-lymphocyte ratio-negative patients, 10 were FN, and 116 were TN (p=0.0001). Overall sensitivity was 89.25%, specificity was 87.88%, Positive and negative predictive values were 83.84% and 92.06% Conclusion: The diagnostic precision of platelet-lymphocyte ratio in forecasting the extent of acute biliary pancreatitis during the early diagnostic stage is quite high.